Immaginari pop e corpi mutanti : Madonna, Björk, Lady Gaga tra arti visive e biotecnologie - Ravesi, Giacomo (Scenari, 2021)
The paper focuses on the music videos of three icons of contemporary pop music: Madonna, Björk and Lady Gaga. The area of interest is the transfiguration of the singers physicality in a mutant physicality, in which come the figurative and conceptual motifs elaborated in the system of visual arts, media and current biotechnologies. In different decades and according to alternative values and representative systems but complementary, the iconography of the pop stars goes through a post-human period, in which the visual image of the singer is re-read according to an horizon, from time to time, science fiction, cyberpunk and post-organic; and in which anachronistic references are merged with high-tech technological images.